Urinary biomarkers of flame retardant exposure among collegiate U.S. gymnasts - Carignan, Courtney C. (2016)
Flame retardants are widely used in polyurethane foam materials including gymnastics safety equipment such as pit cubes and landing mats. We previously reported elevated concentrations of flame retardants in the air and dust of a U.S. gymnastics training facility and elevated PentaBDE in the serum of collegiate gymnasts. Our objective in this pilot study was to compare urinary biomarkers of exposure to other flame retardants and additives of polyurethane foam including tris(1,3-dichloro-2-propyl) phosphate (TDCIPP), triphenyl phosphate (TPHP) and 2-ethylhexyl- 2,3,4,5-tetrabromobenzoate (EH-TBB) in samples collected from 11 collegiate gymnasts before and after a gymnastics practice (n = 53 urine samples total). We identified a 50% increase in the TPHP biomarker (p = 0.03) from before to after practice, a non-significant 22% increase in the TDCIPP biomarker (p = 0.14) and no change for the EH-TBB biomarker. These preliminary results indicate that the gymnastics training environment can be a source of recreational exposure to flame retardants. Such exposures are likely widespread, as we identified flame retardants in 89% of foam samples collected from gyms across the U.S.